Spillovers from the ECB's non-standard monetary policies on non-euro area EU countries: evidence from an event-study analysis - Matteo Falagiarda; Peter McQuade; Marcel Tirpák (European Central Bank (ECB), 2015)
Using event-study techniques we investigate the presence and the magnitude of spillovers from the ECB's non-standard monetary policies on financial assets in selected non-euro area EU countries from Central and Eastern Europe (the Czech Republic, Hungary, Poland and Romania). Generally, we find strong evidence of spillover effects from the ECB's announcements on bond yields. We also find that the SMP announcements resulted in significant spillovers, while those from the OMT and the PSPP announcements were rather limited. Turning to the transmission channels, we argue that spillovers from the SMP announcements went through the portfolio rebalancing and the signalling channels. The transmission of the OMT operated via the confidence channel and for the PSPP we find evidence that both the confidence and the signalling channels were at play.
Keywords: C32; E52; E58; 330; Central and Eastern Europe; ECB; event-study; monetary policy spillovers